2019
DOI: 10.1287/deca.2018.0388
|View full text |Cite
|
Sign up to set email alerts
|

Improving Accuracy by Coherence Weighting of Direct and Ratio Probability Judgments

Abstract: Human forecasts and other probabilistic judgments can be improved by elicitation and aggregation methods. Recent work on elicitation shows that deriving probability estimates from relative judgments (the ratio method) is advantageous, whereas other recent work on aggregation shows that it is beneficial to transform probabilities into coherent sets (coherentization) and to weight judges' assessments by their degree of coherence. We report an experiment that links these areas by examining the effect of coherenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…We explored competing analytic methods, including ACH and FBT, and competing post-analytic methods, including coherentization using different constraints as well as equal-weighted aggregation versus a variety of coherenceweighted aggregation. Consistent with Fan et al (2019), our findings indicate that researchers and practitioners alike who seek to improve judgment accuracy should consider the performance of ensembles of methods. Consider ACH: on its own it was the least effective method, actually reducing accuracy and coherence compared to a within-subject no-method control.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We explored competing analytic methods, including ACH and FBT, and competing post-analytic methods, including coherentization using different constraints as well as equal-weighted aggregation versus a variety of coherenceweighted aggregation. Consistent with Fan et al (2019), our findings indicate that researchers and practitioners alike who seek to improve judgment accuracy should consider the performance of ensembles of methods. Consider ACH: on its own it was the least effective method, actually reducing accuracy and coherence compared to a within-subject no-method control.…”
Section: Discussionsupporting
confidence: 82%
“…In this research, using multiple constraints-namely, unitarity and additivity-paid off (see also Karvetski et al, 2013b). However, other studies have found better results when only the unitarity constraint is applied (Fan et al, 2019;. Although we cannot explain this variability at this time, it is clear that the largest effect is between any form of coherentization and none.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Contributions on elicitation and aggregation can range from behavioral experiments (Fan et al 2019, Schneider et al 2019 to mathematical methods or heuristics (Huang and Bickel 2019). Such papers could have been characterized as methodological or behavioral, but we highlight them in a separate category because elicitation is of central importance to the practice and continued improvement of expected-utility decision theory.…”
Section: Elicitation Methods and Approachesmentioning
confidence: 99%